On rubberized engineered cementitious composites (R-ECC): A review of the constituent material - Al-Fakih, A. (Elsevier Ltd, 2021)
Researchers have used crumb rubber in the manufacturing of engineered cementitious composites (ECC) as a solution for spalling, however, it reduces the mechanical and physical properties. Therefore, this research reviews the available and related literature reviews on rubberized ECC and its constituent. The role of each constituent in a rubberized ECC mix is also reviewed. It's concluded that utilizing rubberized ECC helps to solve environmental issues relating to improper disposal of tyres. As a result, fly ash has been the most common substance utilized in rubberized ECC by scholars all over the world over the past years because of its encouraging impacts on rheology, matrix toughness control, and interactive effect between fiber and matrix. It's also found that the rectification of the crumb rubber drawbacks in ECC is by incorporating a modern method of adopting nano-silica, Polyvinyl alcohol (PVA) fibers, graphene oxide into the rubberized ECC mixes. Therefore, rubberized ECC can be utilized for civil engineering applications, especially with the inclusion of nano-silica and graphene oxide, as a result of its high ductility and low permeability. Â© 2021 The Author(s)